Analisis Normatif Pengabulan Isbat Nikah Tanpa Kemaslahatan Mendesak: Tinjauan Maqashid Al-Ghazali dan Teori Tujuan Hukum Radbruch - Khairiyah, Khairiyah; Nasaruddin, Nasaruddin; Jumat, Gani (Lembaga Teewan Journal Solutions, 2026)
This study examines the Decision of the Palu Religious Court Class IA Number 199/Pdt.P/2025/PA.Pal, which granted an application for isbat nikah (marriage legalization) despite the fact that Applicant II was only 16 years and 7 months old at the time the marriage took place—far below the minimum age limit of 19 years as stipulated in Law Number 16 of 2019—without explicit elaboration regarding urgent public benefit (kemaslahatan mendesak) in the legal reasoning. Using an empirical juridical approach with a qualitative method, data were collected through in-depth interviews with two informants and document analysis of the court decision. The analysis employed two theoretical frameworks: Al-Ghazali’s theory of maslahah and Radbruch’s theory of the objectives of law. The findings reveal three normative failures in the judges’ legal reasoning: negligence in age verification resulting in three different age data versions within a single decision; disregard for the hierarchy of norms, where Law Number 16 of 2019 was not mentioned even once; and the absence of an assessment of urgent public benefit as the material threshold for isbat nikah. From the perspective of Al-Ghazali’s maqashid, three of the five essential objectives of sharia at the dharuriyyah level were not fulfilled. From the perspective of Radbruch’s theory, the decision suffers deficits in all three fundamental legal values: justice, utility, and legal certainty. This study concludes that Islamic law and Indonesian positive law are not contradictory but rather complementary in their shared orientation toward protecting vulnerable parties.